PENERAPAN METODE PROFILE MATCHING UNTUK PENENTUAN SEPEDA MOTOR HONDA MATIC TERBAIK BERDASARKAN PREFERENSI KONSUMEN - Budi Santoso; Erlin Elisa (LPPM Universitas Putera Batam, 2025)
Motorbikes are currently a very popular means of transportation as vehicles for various daily activities. So far, consumers only buy through recommendations from local people when buying motorbikes. This causes many consumers to lack knowledge about the motorbike specifications that are most suitable for each consumer's needs. So we need an approach that can help consumers determine the motorbike that best suits their needs based on assessing aspects of consumers who have been using it for a long time. In this research, the calculation method used is profile matching. For this research, an assessment analysis was carried out on 6 types of Honda motorbikes based on aspects of design, comfort, performance, features, fuel efficiency, price balance and the need for user experience, aesthetic appearance and price match with complete features. For the results of the analysis using the profile matching method, the score with the highest ranking was the Honda Scoopy which received the highest score in all aspects and for various needs such as user experience, aesthetic appearance, and price match with complete features. The Honda PCX and Vario are ranked second and third and could also be the second choice because they have an insignificant difference in value with the Honda Scoopy. Furthermore, Honda PCX, Genio and Beat can also be choices if adjusted to individual needs.